2018
DOI: 10.1097/ogx.0000000000000562
|View full text |Cite
|
Sign up to set email alerts
|

New Labor Management Guidelines and Changes in Cesarean Delivery Patterns

Abstract: Background-In 2010 the Consortium on Safe Labor published labor curves. It was proposed that the rate of cesarean delivery (CD) could be lowered by avoiding the diagnosis of arrest of dilation before 6 cm. However, there is little information on the uptake of the guidelines and on changes in CD rates that may have occurred.Objective-To test the hypotheses that: 1) among patients laboring at term, rates of arrest of dilation disorders have decreased leading to a decrease in the rate of CD; 2) in the second stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 0 publications
2
35
0
Order By: Relevance
“…Others have focused on evaluation of the impact of new labour definitions on labour outcomes interventions. Two observational studies conducted in the USA yielded to different findings in terms of frequency of maternal and neonatal morbidity, and reduction of caesarean sections . There is a need to assess the added value of different designs of labour monitoring tools in the improvement of birth outcomes and reduction of unnecessary interventions during labour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have focused on evaluation of the impact of new labour definitions on labour outcomes interventions. Two observational studies conducted in the USA yielded to different findings in terms of frequency of maternal and neonatal morbidity, and reduction of caesarean sections . There is a need to assess the added value of different designs of labour monitoring tools in the improvement of birth outcomes and reduction of unnecessary interventions during labour.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need to assess the added value of different designs of labour monitoring tools in the improvement of birth outcomes and reduction of unnecessary interventions during labour. This should also include cost‐benefit analysis, considering the potential reduction in unnecessary interventions …”
Section: Discussionmentioning
confidence: 99%
“…The investigators found no difference in CD rate after the guidelines despite the increase in time spent at final cervical dilation from 3.8 hours in 2010 to 5.2 hours in 2014 (p ¼ 0.02). 12 The authors did not assess the rate of compliance with the new guidelines during the study period.…”
Section: Resultsmentioning
confidence: 99%
“…8 However, during the last 3 years, only a modest decrease of 0.9% has been reported, placing the rate of CD at 32.0% in 2015. 9 Several studies have evaluated the impact of the new guidelines on the primary CD rate, [10][11][12] there is a paucity of data describing adherence to the labor arrest guidelines. Our objective was to evaluate the degree of adherence to consensus guidelines in labor arrest disorders management and to compare outcomes between deliveries considered adherent to the guidelines versus those considered not adherent in a single tertiary center.…”
mentioning
confidence: 99%
“…However, it was not obvious whether the new guidelines would actually result in better outcomes for laboring people and their newborns. Observational studies of hospitals that implemented new guidelines produced contradictory results in terms of cesarean births and perinatal outcomes . Need for randomized clinical trials to evaluate the new guidelines was clear.…”
Section: Is the New 4 But Does It Matter?mentioning
confidence: 99%